Analisis Pemodelan Pemilihan Moda Transportasi Ke Kampus oleh Mahasiswa Universitas Muhammadiyah Aceh - Azka, Cut Nawalul; Hidayat, Rifki; Ramadhana, Wahyu (Tameh, 2021)
The Study on the Selection of Mode of Transportation to Campus by Students of the University of Muhammadiyah Aceh to identify the characteristics of the choice of transportation mode and determine the factors that influence students in choosing the mode of transportation to campus. This study was conducted using the Binomial Logit modeling on the characteristics of the choice of transportation mode by students that affect the choice of transportation mode by students of the University of Muhammadiyah Aceh using the SPSS statistic V.24.0 application. Based on the most influential factor in the choice of mode to campus by students of the University of Muhammadiyah Aceh is the ownership of private vehicles, where each student prefers a private vehicle (motorcycle) obtained the equation Y = 0.311 + 0.239(X4) + 0.435(X8). This equation has a strong correlation with R which is 0.630 and the coefficient of determination (R2) is 0.397. This model can be interpreted that for every increase in the number of vehicle owners, there will be an increase in users of private transportation modes by 0.239 and every increase in ownership of private vehicles, there will be an increase in users of private transportation modes by 0.435. From the results of the modeling equation, the probability of students choosing private transportation modes reaches 72.8% Private vehicles. While the probability of students choosing public transportation mode reaches 42.3% occurs when students do not have a driver's license and private vehicle.